Reimagining post-pandemic workplace culture to foster psychological well-being in Bhutan - Rinchen, Kinley; Banham, Vicki; Pelden, Sonam (Bhutan Journal of Research and Development, 2025)
In the wake of the pandemic, Bhutan initiated a series of reforms with the vision of creating an Enlightened Entrepreneurial Bureaucracy (E2B). The unprecedented experiences of the COVID-19 pandemic presented an opportunity to promote psychological well-being in the workplace through heightened health and psychosocial support, offering a chance for reflection to pursue this new vision. Accordingly, the objective of the paper is to reflect on the initiatives taken in response to increased pandemic-related emotional distress in the workplace, with the recognition of the centrality of organisational culture to innovation and productivity. A qualitative approach based on an intra-method convergent design was employed, utilising data collected from interviews and published studies. Results showed that while the pandemic has highlighted the importance of psychological well-being, post-pandemic workplace practices have not yet fully adopted these lessons. Therefore, to contribute to the vision of E2B, the study offers specific, actionable suggestions for workplace policies and practices to promote an organisational culture that fosters psychological well-being. Deliberative interventions to replace complacency with meritocracy and eliminate hostile workplace environments to foster trust, lifelong learning, and employee autonomy are highlighted. Additionally, the paper aims to contribute to the broader discussion on promoting well-being in the post-pandemic era.